DEVELOPMENT OF QUALITY CONTROL PARAMETERS OF CLASSICALLY DRIED AND LYOPHILIZED LEAF POWDER OF VASA (JUSTICIA ADHATODA L.) - Khunt Hiral N.; Umretia Bharti (International Journal of Applied Ayurved Research, 2020)
Introduction: Vasa (Justicia adhatoda L.) is a very common growing plant in the surroundings and used to treat the diseases of human kinds since thousands of years. Quality standard parameters are an essential tool for accurate identification, authentication and standardization of Ayurvedic formulations. In present study, powder of Justicia adhatoda L. leaves was prepared by classical shade drying and lyophilization. The study is an attempt to develop and compare the quality control parameters of classically dried and lyophilized leaf powder of Vasa by using scientific approaches and also assess the effect of both drying methods on quality parameters. Materials & Methods: Fresh Vasa leaves were manually collected for preparation of shade drying and lyophilization. Both the samples were packed in LDPE (Low Density Polyethylene) container and stored under controlled temperature. Pharmacognostic, Physico-chemical parameters, Assay of Vasicine, Limit test for heavy metals and microbial limit test were evaluated for both the samples. Results: Microscopic evaluation of fresh leaf of Vasa and both the powders revealed the similarity of characters. Values of Physico-chemical parameters of both the powders were within the limit mentioned in Ayurvedic Pharmacopeia of India but better in lyophilized powder. Assay of Vasicine shows that no significant differences are found in both samples, while it was decreased up to 60% from at six months in both samples. Conclusion: Present study was help to asses a standard for the identity of Vasa leaves and the obtained data for both the powders can be considered the developed quality standard.